Characteristics of NaCl and water transport in the renal proximal tubule - Kokko, Juha P. (1971)
Renal proximal tubular transport of salt and water has been examined using isolated perfused rabbit tubules. In this method direct measurements can be made under controlled conditions not readily achieved in vivo. The results are in general agreement with previous micropuncture studies in other species, supporting the validity of both sets of measurements. In the present studies, absorption of sodium salts and water occurred without change in the concentration of Na in the lumen except when a poorly reabsorbed solute (raffinose) was present, in which case, mean concentration of Na in the lumen reached a steady-state value 33-35 mEq liter(-1) less than in the bath. The tubule is very permeable to sodium salts (sodium permeability = 9.3 × 10(-5) cm sec(-1), σ(NaCl) = 0.68-(0.71) and to water (hydraulic conductivity [L(p)] = 2.9 to 6.3 × 10(-5) cm sec(-1) atm(-1)). Net reabsorptive flux of Na was only 20% of the unidirectional Na flux. The steady-state concentration difference for Na in the presence of raffinose and σ(NaCl) in the present studies was the same as previously found by micropuncture in the rat. On the other hand Na permeability, net Na transport rate, and L(p) were all from one-half to one-third as great in the isolated rabbit tubule as in the rat in vivo. Apparently, although the transport mechanisms appear to be basically the same in the two species, there are fewer transport units and passive permeability paths per unit length in the rabbit tubule than in the rat.